2016
DOI: 10.1002/stem.2270
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Balancing Stem Cell Self-Renewal and Differentiation with PLZF

Abstract: In recent years, the highly conserved promyelocytic leukemia zinc finger (PLZF, also known as ZBTB16, ZNF145) has attracted attention as a multifunctional transcription factor involved in major biological processes during development. As a transcription factor, PLZF shows tight regulation in its cell-type-specific and stage-specific expression patterns. Emerging evidence shows that PLZF regulates the balance of self-renewal and differentiation in stem cells. However, the gene regulatory network of PLZF is only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 95 publications
3
54
0
Order By: Relevance
“…For instance, downregulation of ZBTB16 would promote inflammation and proliferation of autoreactive T cells [21]. In contrast to the reduced ZFP36 expected to promote satellite cell activation, the increased CITED2 would be expected to reduce satellite cell activation [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, downregulation of ZBTB16 would promote inflammation and proliferation of autoreactive T cells [21]. In contrast to the reduced ZFP36 expected to promote satellite cell activation, the increased CITED2 would be expected to reduce satellite cell activation [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MUC1 in clinically tumor free tissue thus could play a dual role in cancer development. ZBTB16, zinc finger and BTB domain containing 16 (also known as PLZF or ZNF145), is a transcription factor involved in balancing stem cell self-renewal and differentiation and is tightly regulated in cell-type and developmental stage-specific manners [28]. Reactivation of factors involved in development is often seen in tumors, accordingly this factor could also have a dual tumor stimulatory role through stem cell renewal and/or inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (5,7) showed that PLZF is strongly expressed in hematopoietic stem cells (HSCs) and immature progenitors. While Plzf is essential for self-renewal in spermatogenesis, it is not indispensable for normal hematopoiesis (8), but is involved in control of HSC homeostasis (9). In malignant hematopoiesis, we found that Plzf is critically involved in the aberrant self-renewal program induced by mixed lineage leukemia (MLL) fusion oncogenes (10).…”
mentioning
confidence: 94%